Antimicrobial Peptides: Their Role in Innate Immune System and Usage in Future Drug Development - Tristia Rinanda (Syiah Kuala University, 2015)
Antimicrobial peptides naturally play a role in the innate immune system of any living organisms. These small molecules are known as